2021
DOI: 10.1002/ajh.26191
|View full text |Cite
|
Sign up to set email alerts
|

Daratumumab, lenalidomide, and dexamethasone in systemic light‐chain amyloidosis: High efficacy, relevant toxicity and main adverse effect of gain 1q21

Abstract: The genomic landscape of Waldenström macroglobulinemia is characterized by highly recurring MYD88 and WHIM-like CXCR4 mutations, and small somatic deletions associated with B-cell lymphomagenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…One patient without haematological response at 6 months from DRd treatment had chromosome 1q21 amplification. A previous publication reporting the efficacy of DRd regimen against relapsed or refractory systemic AL amyloidosis patients, indicated that the existence of 1q21 amplification may reduce the efficacy of DRd 14 . Although the precise mechanisms of low treatment response are unclear, patients with 1q21 amplification may need to consider regimens other than DRd.…”
Section: Characteristic N = 10mentioning
confidence: 99%
“…One patient without haematological response at 6 months from DRd treatment had chromosome 1q21 amplification. A previous publication reporting the efficacy of DRd regimen against relapsed or refractory systemic AL amyloidosis patients, indicated that the existence of 1q21 amplification may reduce the efficacy of DRd 14 . Although the precise mechanisms of low treatment response are unclear, patients with 1q21 amplification may need to consider regimens other than DRd.…”
Section: Characteristic N = 10mentioning
confidence: 99%
“…Probably, due to the low CD38 level, patients with 1q21 gain achieved less satisfactory outcomes than those without this genetic aberration when daratumumab-containing regimens were adopted [ 30 , 66 ]. One study investigating the impact of 1q21 on the standard melphalan/dexamethasone treatment also demonstrates that 1q21 is an independent adverse prognostic factor for survival [ 35 ].…”
Section: Secondary Genetic Eventsmentioning
confidence: 99%
“…The main side effects are fluid retention, increase of NT-ProBNP and marked hypotension [27]. However, it is quite effective if used as upfront or relapse treatment in combination with dexamethasone or with alkylating agents [28] or with the monoclonal antibody daratumumab (DRD) [29]. Gain of 1q21 had an adverse impact on treatment results [27,29].…”
Section: Immunomodulatory Agents (Imids)mentioning
confidence: 99%
“…However, it is quite effective if used as upfront or relapse treatment in combination with dexamethasone or with alkylating agents [28] or with the monoclonal antibody daratumumab (DRD) [29]. Gain of 1q21 had an adverse impact on treatment results [27,29]. In DRD treated AL patients calculated median hemEFS and OS were 17.4 and 29.1 months, respectively.…”
Section: Immunomodulatory Agents (Imids)mentioning
confidence: 99%